2020
DOI: 10.1007/s11227-020-03518-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of multi-container deployment schemes for HPC workloads: an empirical study

Abstract: The High-Performance Computing (HPC) community has recently started to use containerization to obtain fast, customized, portable, flexible, and reproducible deployments of their workloads. Previous work showed that deploying an HPC workload into a single container can keep bare-metal performance. However, there is a lack of research on multi-container deployments that partition the processes belonging to each application into different containers. Partitioning HPC applications have shown to improve their perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The continuous involvement of containers in HPC created a new research direction of multi-container deployment schemes for HPC. Peini et al [237] compared and analyzed multi-container development schemes based on Docker and Singularity on two different platforms: UMA and NUMA and showed that Docker and Singularity container technology has performance overhead for MPI when running on multiple containers. Research work [238] used Kubernetes on HPC and compared the performance against Docker Swarm and bare metal.…”
Section: A Containers In Hpcmentioning
confidence: 99%
“…The continuous involvement of containers in HPC created a new research direction of multi-container deployment schemes for HPC. Peini et al [237] compared and analyzed multi-container development schemes based on Docker and Singularity on two different platforms: UMA and NUMA and showed that Docker and Singularity container technology has performance overhead for MPI when running on multiple containers. Research work [238] used Kubernetes on HPC and compared the performance against Docker Swarm and bare metal.…”
Section: A Containers In Hpcmentioning
confidence: 99%
“…Moreover, they provided a rule to decide the number of containers per pod by considering the characteristics of the application. Our previous papers [12] [13] demonstrated through standalone executions that some types of containerized HPC applications achieve better performance when exploiting multi-container deployments which partition the processes that belong to each application into multiple containers in each node, and when constraining each of those containers to a single NUMA domain or pinning them to specific processors. These works show some ways to achieve better performance for HPC workloads in the Cloud, but those insights have not yet been integrated and utilized by the current Cloud orchestrators.…”
Section: Deployment and Scheduling Schemes For Containerized Hpc Work...mentioning
confidence: 99%
“…Our previous systematical performance studies [12] [13] have demonstrated through standalone executions that some types of containerized HPC applications achieve better performance when exploiting multi-container deployments which partition the processes that belong to each application into multiple containers in each node and when constraining each of those containers to a single NUMA (Non-Uniform Memory Access) domain or pinning them to specific processors. However, these deployment schemes have not yet been integrated in multiprogrammed environments for HPC workloads by current Cloud orchestrators.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [16], we enabled the interconnection across hosts through TCP/IP protocol between Singularity instances running Big Data applications. Moreover, in our latest work [3], we performed a performance analysis of multi-container deployments with different container granularity for a number of HPC applications, but only with a single host and the TCP/IP protocol.…”
Section: Related Workmentioning
confidence: 99%
“…Following the trend of Cloud computing, the HPC community has also started to adopt containerization instead of hardware virtualization to benefit from some of its wellknown advantages [1], such as the encapsulation of specific software environments for each user, which allows for customization, portability, and research reproducibility; the isolation of users from the underlying system and from other users, which allows for security and fault protection; and the agile and fine-grain resource allocation and balancing, which allows for efficient cluster utilization and failure recovery [2,3].…”
Section: Introductionmentioning
confidence: 99%